Productivity Dispersion in Medicine and Manufacturing - Chandra, Amitabh; Finkelstein, Amy; Sacarny, Adam; Syverson, Chad (American Economic Review, 2016)
The conventional wisdom in health economics is that large differences in average productivity across US hospitals are the result of idiosyncratic features of the healthcare sector which dull the role of market forces. Strikingly, however, we find that productivity dispersion in heart attack treatment across hospitals is, if anything, smaller than in narrowly defined manufacturing industries such as ready-mixed concrete. While this fact admits multiple interpretations, it suggests that healthcare may have more in common with “traditional” sectors than is often assumed, and relatedly, that insights from research on productivity and allocation in other sectors may enrich analysis of healthcare.